Conventional protein kinase C isoenzymes undergo dephosphorylation in neutrophil-like HL-60 cells treated by chelerythrine or sanguinarine - Vrba, Jiří; Dvořák, Zdeněk; Ulrichová, Jitka; Modrianský, Martin (Cell biology and toxicology, 2008)
The quaternary benzo[c]phenanthridine alkaloid chelerythrine is widely used as an inhibitor of protein kinase C (PKC). However, in biological systems chelerythrine interacts with an array of proteins. In this study, we examined the effects of chelerythrine and sanguinarine on conventional PKCs (cPKCs) and PKC upstream kinase, phosphoinositide-dependent protein kinase 1 (PDK1), under complete inhibition conditions of PKC-dependent oxidative burst. In neutrophil-like HL-60 cells, sanguinarine and chelerythrine inhibited N-formyl-Met-Leu-Phe, phorbol 12-myristate 13-acetate (PMA)-, and A23187-induced oxidative burst with IC(50) values not exceeding 4.6 micromol/L, but the inhibition of PMA-stimulated cPKC activity in intact cells required at least fivefold higher alkaloid concentrations. At concentrations below 10 micromol/L, sanguinarine and chelerythrine prevented phosphorylation of approximately 80 kDa protein and sequestered approximately 60 kDa phosphoprotein in cytosol. Moreover, neither sanguinarine nor chelerythrine impaired PMA-stimulated translocation of autophosphorylated PKCalpha/betaII isoenzymes, but both alkaloids induced dephosphorylation of the turn motif in PKCalpha/betaII. The dephosphorylation did not occur in unstimulated cells and it was not accompanied by PKC degradation. Furthermore, cell treatment with sanguinarine or chelerythrine resulted in phosphorylation of approximately 70 kDa protein by PDK1. We conclude that PKC-dependent cellular events are affected by chelerythrine primarily by multiple protein interactions rather than by inhibition of PKC activity.
Keywords: Isoquinolines; vztah mezi dávkou a účinkem léčiva; HL-60 buňky; Cell-Free System; Respiratory Burst; Substrate Specificity; bezbuněčný systém; lidé; alkaloidy; Protein Transport; Protein Serine-Threonine Kinases; HL-60 Cells; isochinoliny; buněčná smrt; NADPH-oxidasy; transport proteinů; respirační vzplanutí; Dose-Response Relationship, Drug; fosforylace; Alkaloids; Protein Kinase C; Cell Death; Benzophenanthridines; Neutrophils; neutrofily; benzofenantridiny; NADPH Oxidases; Isoenzymes; substrátová specifita; protein-serin-threoninkinasy; izoenzymy; Phosphorylation; proteinkinasa C; Humans